2011
DOI: 10.1177/0269216311410900
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of dying, death and bereavement in motor neurone disease: A qualitative study

Abstract: this study has identified a number of issues people with MND and their carers face in the final stages of the illness, indicating some ways in which health, social and palliative care services could be improved or co-operate more effectively in order to better meet their needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
168
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(174 citation statements)
references
References 42 publications
1
168
0
Order By: Relevance
“…In this study caregivers' and patients' alike experienced a wide range of fears and anxieties regarding the final stages of the disease similar to those documented by Whitehead, et al [43]. The impending death of a loved one can give rise to a wide range of emotional experiences which occur before death and are collectively known as anticipatory grief.…”
Section: Discussionsupporting
confidence: 69%
“…In this study caregivers' and patients' alike experienced a wide range of fears and anxieties regarding the final stages of the disease similar to those documented by Whitehead, et al [43]. The impending death of a loved one can give rise to a wide range of emotional experiences which occur before death and are collectively known as anticipatory grief.…”
Section: Discussionsupporting
confidence: 69%
“…There is little detailed published information about what happens to patients using NIV as they deteriorate and die, thus making informed consent and general sharing of information with patient and families difficult 12. Better development of advance care planning (ACP) processes is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Interviews with patients on assisted ventilation in the USA (mostly receiving this via tracheostomy) found that while most patients wanted to issue a direction in advance about circumstances in which they would wish to stop assisted ventilation, few had had the opportunity to do so 11. Whitehead et al 12 explored end of life decision making with patients and with bereaved carers in Preston, UK, and identified a need for more information and shared decision making, but there is little other literature exploring this area in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, they comprised purposive sampling of family carers of people with MND resident in Northwest England, exploring experiences of accessing health, social and palliative care services18 22 or experiences using the Preferred Priorities for Care (PPC) document 19. Similar methodological approaches were adopted in the original studies with data collected using prompts within narrative-style interviews.…”
Section: Methodsmentioning
confidence: 99%